2010
DOI: 10.21608/eajbsf.2010.17457
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of citric acid and their soluble powder formulations against Aphis craccivora under laboratory conditions.

Abstract: Anionic surfactant sodium dodecyl sulphat (SDS) was used as wetting agent to prepare citric acid as soluble powder formulation. The prepared formulation showed stability and passed successfully all physico-chemical properties for soluble powder formulations. The insecticidal activity of active ingredient and its formulations were compared with citric acid (SP 90%) that prepared by El-kady (2008) through using non-ionic surfactant against different stages of Aphis craccivora under laboratory conditions. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Furthermore, (20) reported that few makeup products like citric acid were applied to the skin of rats, mosquitoes were attracted towards, the results showed that Anopheles gambae was less attracted than Aedes aegypti towards the makeup products. The current study is similar to those conducted by (8), in which the citric acid was found to be effective on all tested stages of Aphis craccivora. This effectiveness was barely noticed after 2 hours, yet it increased after 12 hours .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, (20) reported that few makeup products like citric acid were applied to the skin of rats, mosquitoes were attracted towards, the results showed that Anopheles gambae was less attracted than Aedes aegypti towards the makeup products. The current study is similar to those conducted by (8), in which the citric acid was found to be effective on all tested stages of Aphis craccivora. This effectiveness was barely noticed after 2 hours, yet it increased after 12 hours .…”
Section: Resultssupporting
confidence: 86%
“…The successful use of active components depends on its correct formulation into an equipment which can be applied for output protection with safety to those applying materials to the environment and to human, and animal life (7)(8)(9). Researchers have recently turned to the use of alternatives to pesticides that are effective against insects that remain for a short period and are safe and cheap, such as inorganic salts and antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this research paper was to determine the acaricidal efficacy of three formulations for three safe compounds derived from plants, jojoba oil 90 % EC and the previously prepared Baraka oil 75 % EC [22] and citric acid 90 % SP [23][24][25] on T. urticae. In order to move a new step in our ongoing program for obtaining new, safe and eco-friendly active ingredients and formulating it in a local formulation to be used for pest control after completing the necessary required studies.…”
Section: Introductionmentioning
confidence: 99%